2019
DOI: 10.3920/bm2017.0178
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum IS-10506 supplementation increases faecal sIgA and immune response in children younger than two years

Abstract: The immature intestinal immune system in young children develops as it comes into contact with dietary and microbial antigens in the gut. Intestinal microbiota plays a significant role in host defence mechanisms as shown by inflammatory responses towards potential pathogens. We investigated the probiotic function of Lactobacillus plantarum IS-10506 of ‘dadih’ origin in modulating immune response in young children. We aimed to assess its effect on their immune response by assessing transforming growth factor-β1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…Lpb. plantarum IS-10506, from danhi, was successfully administered as a dietary early intervention to stimulate humoral and intestinal immune response in healthy preschool children [192,193], as well as to treat children affected by atopic dermatitis, a chronic recurrent inflammatory skin disease characterized by an immunity dysregulation [194]. The capacity to ameliorate quality of life in patients affected by atopic dermatitis via inflammation reduction and the immunomodulatory effects (i.e., IgE attenuation, reduction in eosinophil count) of Lpb.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Lpb. plantarum IS-10506, from danhi, was successfully administered as a dietary early intervention to stimulate humoral and intestinal immune response in healthy preschool children [192,193], as well as to treat children affected by atopic dermatitis, a chronic recurrent inflammatory skin disease characterized by an immunity dysregulation [194]. The capacity to ameliorate quality of life in patients affected by atopic dermatitis via inflammation reduction and the immunomodulatory effects (i.e., IgE attenuation, reduction in eosinophil count) of Lpb.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In another study using L. plantarum IS-10506 from dadih as well, it was reported that the increasing production of sIgA in children younger than two years was observed, due to the stimulation of TGF-β1 by L. plantarum IS-10506 supplementation. This result was associated with a significant correlation between TGF-β1/TNF-α and fecal sIgA [69].…”
Section: Immunomodulatory Propertiesmentioning
confidence: 76%
“…In addition, dadih also contains secondary metabolite such as lactic acid, acetic acid, and antibiotic compounds such as acidophylline, acidolin, nicin, and bulgarican which can prevent the growth of pathogenic microbes and destructive microbes. 11 Surono et al 17 showed probiotic Lactobacillus plantarum IS-10506, supplementation isolated from dadih can stimulate TGF-β1, which in turn increases the production of IgA. The purpose of this study was to investigate the effects of dadih on the intestinal immune response based on pro-inflammatory and antiinflammatory cytokine production.…”
Section: Introductionmentioning
confidence: 95%